Water Quality Assessment of Begnas and Rupa Lakes, Lesser Himalaya Pokhara, Nepal - Pant, Ramesh R.; Pal, Khadka Bdr.; Adhikari, Nanda L.; Adhikari, Subash; Mishra, Akkal D. (Journal of the Institute of Engineering, 2019)
This study was conducted to assess water quality variations and identify potential pollution sources in two lakes namely Begnas and Rupa, Lesser Himalayas Pokhara, Nepal during monsoon season in June 2016. A total of 18 water samples (n= 9, from each lake) were collected and major physicochemical parameters were analyzed: pH, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), biological oxygen demand (BOD), nitrate-nitrogen (NO3-N), phosphate- phosphorus (PO4-P), ammonia, chloride, free CO2 and total hardness (TH).The results revealed that the water of both lakes were relatively pure with very less TDS as compared to other lakes considered for the comparison with this study. However, the concentrations of CO2 and phosphates were found to be higher than WHO guidelines for drinking water and also indicated the problem of rapid eutrophication in both of the lakes. Thus, the higher concentrations of organic pollutants and the rapid eutrophication process could be the serious threats that should be considered by the concerned authorities for the sustainability of the lakes in future.